Do green transport and mitigation technologies drive OECD countries to sustainable path?. (May 2023) - Khurshid, Adnan; Khan, Khalid; Chen, Yufeng; Cifuentes-Faura, Javier
Graphical abstract: Abstract: The sustainable development initiative aims to combat climate change in which green innovations, renewables, and taxes play a significant role. This study argues that sectoral carbon footprints vary, and so does the impact of technical innovation (Transportation ( MTT ), production and processing ( MTPP ), and Energy generation ( MTEG )) in mitigation efforts. Therefore, the study examines their influence along with taxes in OECD economies from 1990 to 2020. The preliminary assessment uses second-generation techniques, while the long-run relationship among variables is examined using Error-correction-based models because of cross-sectional interdependencies. The findings affirm the existence of long-term linkages between variables. Transport-related innovation (MTT) reduces demand-based (DBE) and GHG emissions by elasticities of 0.115 and 0.126, respectively. Similarly, MTEG and MTPP technologies reduce production-based emission (PBE) by 0.174% and 0.137%, respectively, and GHG by 0.301% and 0.140%. Energy consumption is the major polluter across all sectors, whereas carbon tax limits emissions.